Salvianolic acids and its potential for cardio-protection against myocardial ischemic reperfusion injury in diabetes - Jiang, Yuxin; Cai, Yin; Han, Ronghui; Xu, Youhua; Xia, Zhengyuan; Xia, Weiyi (Frontiers in Endocrinology, 2024)
The incidence of diabetes and related mortality rate increase yearly in modern cities. Additionally, elevated glucose levels can result in an increase of reactive oxygen species (ROS), ferroptosis, and the disruption of protective pathways in the heart. These factors collectively heighten the vulnerability of diabetic individuals to myocardial ischemia. Reperfusion therapies have been effectively used in clinical practice. There are limitations to the current clinical methods used to treat myocardial ischemia-reperfusion injury. As a result, reducing post-treatment ischemia/reperfusion injury remains a challenge. Therefore, efforts are underway to provide more efficient therapy. Salvia miltiorrhiza Bunge (Danshen) has been used for centuries in ancient China to treat cardiovascular diseases (CVD) with rare side effects. Salvianolic acid is a water-soluble phenolic compound with potent antioxidant properties and has the greatest hydrophilic property in Danshen. It has recently been discovered that salvianolic acids A (SAA) and B (SAB) are capable of inhibiting apoptosis by targeting the JNK/Akt pathway and the NF-κB pathway, respectively. This review delves into the most recent discoveries regarding the therapeutic and cardioprotective benefits of salvianolic acid for individuals with diabetes. Salvianolic acid shows great potential in myocardial protection in diabetes mellitus. A thorough understanding of the protective mechanism of salvianolic acid could expand its potential uses in developing medicines for treating diabetes mellitus related myocardial ischemia-reperfusion.